Pojetí stylové příznakovosti v současné české stylistice - Křístek, Michal (Stylistyka, 2000)
The article deals with the terminology concerning the concept of stylistically marked/unmarked means of expression, above all at the level of vocabulary. It surveys both the identical points and the differences ofterms concerning stylistic markedness as they are used in synthetic works focused on Czech stylistics published approximately in the past thirty years. At the end it suggests another classification which tries to stress the hierarchy among the terms concerned and to avoid ambiguity in their use.